Precision Reengineering of the Oral Microbiome for Caries Management. (November 2019) - Baker, J.L.; He, X.; Shi, W.
Technological advancements have revolutionized our understanding of the complexity and importance of the human microbiome. This progress has also emphasized the need for precision therapeutics, as it has underscored the dilemmas, such as dysbiosis and increasing antibiotic resistance, associated with current, broad-spectrum treatment modalities. Dental caries remains the most common chronic disease worldwide, accompanied by a tremendous financial and social burden, despite widespread and efficacious fluoride and hygienic regimens. Over the past several decades, various precision approaches to combat dental caries, including vaccines, probiotics, and antimicrobial compounds, have been pursued. Despite the distinct overall conceptual strengths of each approach, for various reasons, there are currently no approved precision antibiotic therapeutics to prevent dental caries. Specifically targeted antimicrobial peptides (STAMPs) are synthetic molecules that combine the antibiotic moiety of a traditional antimicrobial peptide with a targeting domain to provide specificity against a particular organism. Conjoining the killing domain from the antimicrobial, novispirin G10, and a targeting domain derived from the Streptococcus mutans pheromone, CSP, the STAMP C16G2 was designed to provide targeted killing of S. mutans, widely considered the keystone species in dental caries pathogenesis. C16G2 was able to selectively eliminate S. mutans from complex ecosystems while leaving closely related, yet health-associated, oral species unharmed. This remodeling of the dental plaque community is expected to have significant advantages compared to conventional broad-spectrum mouthwashes, as the intact, surviving community is apt to prevent reinfection by pathogens. Following successful phase I clinical trials that evaluated the safety and basic microbiology of C16G2 treatments, the phase II trials of several C16G2 formulations are currently in progress. C16G2 represents an exciting advance in precision therapeutics, and the STAMP platform provides vast opportunities for both the development of additional therapeutics and the overall study of microbial ecology.